Insulin sensitivity and secretion in youth onset type 2 diabetes with and without visceral adiposity. Issue 1 (July 2015) - Amutha, Anandakumar; Ali, Mohammed K.; Unnikrishnan, Ranjit; Anjana, Ranjit Mohan; Ranjani, Harish; Gokulakrishnan, Kuppan; Mohan, Viswanathan; Narayan, K.M Venkat
Highlights: Insulin secretion and sensitivity measures differ among normal and T2DM when classified based on visceral fat (VF) levels. DIo is considerably lower in people with T2DM than NGT, regardless of VF. DIo was strongly associated with high VF in the T2DM group even after adjusting for Matsuda index, age, BMI and leptin. Lower DIo was seen with increasing 2 PG hour values even among normal glucose tolerant participants. Detecting early pathophysiological changes among "normal" individuals could help initiate preventive measures. Abstract: Aim: To investigate insulin sensitivity and insulin secretion patterns among Asian Indian youth without and with type 2 diabetes (T2DM-y defined as onset of diabetes at or below 25years) with normal and high visceral fat (VF) levels. Methods: We recruited 74 T2DM-y individuals, within 18 months of diagnosis and compared them to 77 age-matched controls with normal glucose tolerance (NGT). Using L4/L5 abdominal CT images, VF levels were categorized as normal or high according to their median values. Oral glucose tolerance tests (glucose and insulin measures) were used to derive Matsuda index, insulin resistance (HOMA-IR) and oral disposition index (DIo). Relationships between measures of insulin sensitivity and secretion and T2DM-y by VF level were assessed using standardized multinomial regression models. Results: Participants were categorized into four groups: NGT-normal VF; NGT-high VF; T2DM-normal VF, and T2DM-high VF. Among NGTs, those with high VF had significantly lower insulin sensitivity (0.013 vs.0.019 pM −1 ) and Matsuda index (10.2 vs.13.8), than normal VF. When compared, T2DM-high VF had lowest insulin sensitivity (0.009 vs.0.019, 0.013, 0.012 pM-1; p < 0.001), Matsuda index (6.4 vs. 13.8, 10.2, 8.6; p < 0.001), OGIS120 (305 vs. 396, 382, 316; p < 0.001) and DIo (0.48 vs. 3.75, 3.20, 0.55 mmol/L; p < 0.001). At every category of 2 h PG values, NGT-high VF had lower DIo than NGT-normal VF participants. In standardized multinomial models, that included DIo and Matsuda index adjusted for age, gender, BMI, and leptin, DIo (Odds ratio: 0.001; 95%Confidence interval: 0.000–0.020), matsuda index (0.26; 0.07–0.93), age (2.92; 1.18–7.19) and leptin (3.17; 1.12–8.99) were associated with high VF among T2DM. Conclusion: Lower DIo and Matsuda index, younger age and higher leptin were independently associated with high visceral fat among T2DM participants. Also, lower DIo was seen with increasing 2 h PG values even among normal glucose tolerant individuals.